Laundrybar / Siti Nurbahiah Adenan - Adenan, Siti Nurbahiah (2022)
LaundryBar is a local company which is focusing on the laundry service. In this company analysis, it is focusing on the machine that used for laundry equipment such as washing machine, dryer and ironers. The SWOT analysis has been conduct for this company where it has been investigate, identified and analysed along with their current problem and come out with solutions. The first problem of the product is extra labor in handling quarter. As we know, the uses of quarter is bit complicated because it need a more time for owner or operator of laundry bar to handle it. This is because the laundry washing machine still rely on the coin operated system. This system is give a more work to the owner because they need to always go to the bank for exchanging the quarter if the quarter is missing or not enough. Therefore, this product also involving to the electricity where it use a high consumption of electricity to make the washing work done quickly. This will give a burden to the owner because the bill or cost of the laundry business will become higher. Then, the product also do not contain a temperature guide for washing clothes. Aside from that, there are a few solution that has been analyse to improve the product. There are three solution has been taken to overcome this problem which is changing the coin operated mechanism to smart paying, apply eco mode to the washing machine and increase the selection for temperature setting. All of the solution are considered to make the company producing a way quality product that to be served to their customer.